2014
DOI: 10.4236/ojim.2014.41006
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged QTc Interval Is an Electrophysiological Hallmark of Cirrhotic Cardiomyopathy

Abstract: BACKGROUND: Cirrhotic Cardiomyopathy is a relatively ill-characterized condition, which is often under-diagnosed due to absence of defined diagnostic criteria. ECG showing corrected QT Interval prolongation is the most suitable available option for diagnosis of this condition. OBJECTIVE: To determine the frequency of corrected QT interval prolongation in patients with liver cirrhosis. METHODOLOGY: Patients (n = 166) with confirmed cirrhosis, 30 years or older, presented in the outpatient and emergency departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
5
2
Order By: Relevance
“…This is close to the results presented by Bernardi et al 27 . However, Zuberi et al 28 and Bhatti et al 3 found the frequency of QTc prolongation was much lower than us. This discrepancy may be explained by the presence of other compounding factors such as electrolyte disturbances, concomitant cardiac problems, or use of QTc prolonging drugs, which were excluded in our study but might have been included in other studies.…”
Section: Discussioncontrasting
confidence: 55%
“…This is close to the results presented by Bernardi et al 27 . However, Zuberi et al 28 and Bhatti et al 3 found the frequency of QTc prolongation was much lower than us. This discrepancy may be explained by the presence of other compounding factors such as electrolyte disturbances, concomitant cardiac problems, or use of QTc prolonging drugs, which were excluded in our study but might have been included in other studies.…”
Section: Discussioncontrasting
confidence: 55%
“…Compared to our cohort which only had 15 patients (11%) classified as CPC C, there were more cases of CPC C in the study of Kumar et al (49%, 36) and Bhatti et al (45%, 77) which are reflective of a more decompensated state [12, 13]. Most of our patients were classified as CPC A (20%, 17) and CPC B (68%, 57) which have better prognosis.…”
Section: Discussioncontrasting
confidence: 50%
“…Prolonged QTc interval has been reported to be an electrophysiological hallmark of cirrhotic cardiomyopathy [13]. Although studies have reported a correlation of the prolongation of the QT interval to the severity of liver cirrhosis, our patients were observed to have prolonged QT interval in the early stages of liver cirrhosis (CPC A or MELD score of 9 or below) and in the late stage of cirrhosis (CPC C).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations